Developing Pedagogical Applications for Teaching Politeness Strategies in Advanced English as a Foreign Language Classrooms - Alshamrani, Ahmed (International Journal of Linguistics, 2023)
The field of English as a foreign language (EFL) strives to promote students' proficiency by equipping them with proper grammatical and lexical skills. However, EFL textbooks often neglect the teaching of pragmatics which can lead to cross-cultural communication failures for EFL learners. EFL learners often struggle with traditional language teaching approaches that prioritize grammatical development over pragmatic skills. This paper aims to address this gap by focusing on promoting the use of politeness strategies among EFL learners in cross-cultural communication, particularly in email correspondences with college professors. The proposed teaching activities are based on the Linguistic Theory of Politeness and the 3Ds framework within the context of the Communicative Repertoire Approach. This paper aims to assist advanced EFL learners in effectively employing politeness strategies when writing email requests to college professors, by offering practical pedagogical applications that enhance EFL learners' ability to express their communicative intentions clearly and avoid any potential misunderstanding or misinterpretation by their college professors.